Her holiday fireman ebook - Y'Barbo, Kathleen (Second Time Around., 2012)
From his first encounter with the feisty redhead, widower and fire marshal Ryan Owen knows he's in trouble. He's in Vine Beach to heal, not to find romance. As for Leah Berry, she's come home strictly to lay claim to her family's restaurant and fend off developers. Leah is infuriated when Ryan shuts down the restaurant on violations. Both are determined to have their way, even as something unexpected starts blossoming between them. They'll need to learn the hardest thing about love and faith—letting go.